Investigating the Quitting Decision of Nurses: Panel Data Evidence from the British National Health Service - Paul Frijters; Michael A. Shields; Stephen Wheatley Price (Institute for the Study of Labor (IZA), 2003)
There is currently a worldwide shortage of registered nurses, driven by large shifts in both the demand for and supply of nurses. Consequently, various policies to increase the recruitment and retention of nurses are under discussion, in particular, the role that wage increases might have in promoting nurse labour supply. In this paper we provide the first detailed empirical investigation into the quitting behaviour of nurses in the British National Health Service (NHS), using a newly constructed longitudinal survey. We fit both single and competing-risks duration models that enable us to establish the characteristics of those nurses who leave the NHS, distinguish the importance of pay in this decision and document the destinations that nurses move to. Contrary to expectations, we find that the hourly wage received by nurses outside of the NHS is around 20% lower than in the NHS, and that hours of work are about the same. However, there is a clear movement away from shift work. Age, seniority, job and employer characteristics are all found to be important predictors of nurses leaving the NHS. However, whilst the effect of wages is found to be statistically significant, the predicted impact of an increase in nurses? pay on retention rates is small. Our main conclusion, therefore, is that the current nurse shortages in the NHS will not be eliminated through substantially increased pay. Rather employers need to identify and address other aspects of the job which are driving nurses? decisions to quit the NHS.
Keywords: I18; J45; J63; 330; nurses; panel data; wages; hours; quitting; NHS; Pflegeberufe; Kündigung; Arbeitsmobilität; Lohn; Schätzung; Großbritannien